2015
DOI: 10.1001/jama.2015.13043
|View full text |Cite
|
Sign up to set email alerts
|

Naproxen With Cyclobenzaprine, Oxycodone/Acetaminophen, or Placebo for Treating Acute Low Back Pain

Abstract: clinicaltrials.gov Identifier: NCT01587274.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 34 publications
3
151
0
9
Order By: Relevance
“…Previous research has shown that functional outcomes are no better for patients with back pain treated with opioids than for those treated with nonsteroidal anti-inflammatory drugs (or other treatment modalities), and current recommendations do not endorse routine prescribing of opioids for this condition. [18][19][20] Independent risk factors that have been associated opioidrelated harms include a history of psychiatric illness or substance use disorder, sleep disorders and the use of nonopioid medications with sedating properties, especially benzodiazepines. [21][22][23] In Research our study, a large number of patients in both the emergency physician and family physician groups had known risk factors associated with adverse outcomes related to opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that functional outcomes are no better for patients with back pain treated with opioids than for those treated with nonsteroidal anti-inflammatory drugs (or other treatment modalities), and current recommendations do not endorse routine prescribing of opioids for this condition. [18][19][20] Independent risk factors that have been associated opioidrelated harms include a history of psychiatric illness or substance use disorder, sleep disorders and the use of nonopioid medications with sedating properties, especially benzodiazepines. [21][22][23] In Research our study, a large number of patients in both the emergency physician and family physician groups had known risk factors associated with adverse outcomes related to opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…Barksdale et al [10] reported that the nurses of the emergency department were trained in pain classification and applied it to reduce the starting time of pain control for the patients who were visiting because of various pains. In addition, in the study comparing the results of various combinations of painkillers to acute non-traumatic back pain patients, the combination of painkillers and the prognosis of the patient was not related, however, regardless of the degree of pain, the early administration of painkillers helps the patient to control pain quickly, it was reported that even gel-type rubon painkillers were effective [11,12]. In the our study, painkillers were administered to all back pain patients, and the time required to administer the painkillers was significantly shorter in patients in the less than 3 hours group.…”
Section: Discussionmentioning
confidence: 99%
“…In acute lower back pain, NSAIDs have been shown to significantly reduce pain and improve daily function [63]. The addition of opioids in this setting of pain was not proven to be more effective than NSAIDs alone [64].…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…Moreover, there is little to no added benefit when using muscle relaxants together with NSAIDs [64,67]. Given the limited data on muscle relaxants, one should consider the side effects.…”
Section: Antispasmotics (Muscle Relaxants)mentioning
confidence: 99%